Acomiztli Netzahualcóyotl ́sCuícatl:between Nahuatl Ritual and Aesthetics - Ortiz Caraballo, Carlos Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article delves into the literary tradition of one of the most established cultures of ancient Mexico: the Aztec Náhuatl culture. In this case, the Cuícatl [songs] of the Aztec Nahuatl prince Acomiztli (1402- 1469) and their main lyric topics are discussed in this article. These writings are interpreted from the point of view of literary anthropology, which understands the text as a fragment of a culture; where the center of the analysis involves the creator-subject and his interaction with the environment. Therefore, we begin with concepts such as Náhuatl culture, cuícatl and religious world view, among others. This study seeks to externalize both the message of freedom and hope delivered by the prehispanic cuica - picqui [songwriter] in his Cuícatl , and the contribution of Aztec Náhuatl culture to Latin American literature.